(untitled) (Brazilian Journal of Health Research, 2019)
Introduction: the present study is an analysis about relationships set between people with mental disorders based on their participation in a particular therapeutic place: the Community Therapy (CT). Objective: understanding how these relationships make it possible for these people to strengthen their affective social ties by creating new bonds, and helping them to face their derangements and stigma. Methods: Data collection through interviews and field diary of visitations to community therapy sessions. Qualitative analysis focused on data content. Results: The analysis allowed the creation of a thematic frame to present efforts made to combat suffering and stigma based on social status equalization, closeness, participation and association aspects. Conclusion: Community therapy represents a comfort space for its participants, it enables the deconstruction of the mental disorder stereotype and helps sociability recovery, a fact that changes the lives of involved people. The present investigation also revealed the importance of therapy to help these patients deal with negative emotions. The therapy provides motivation, self-esteem and well-being; however, without having too deep impact on individuals and on their relationship with the community they live in.